The Abundance of atp Gene Transcript and of the Membrane F(1)F(0)-ATPase as a Function of the Growth pH of Alkaliphilic Bacillus firmus OF4 - Ivey, D. Mack (1994)
Molecular biological and biochemical studies of the F(1)F(0)-ATP synthase of alkaliphilic Bacillus firmus OF4 show that the enzyme used at pH 7.5 and pH 10.5 is a unique product of the atp operon, expressed at the same levels and yielding an enzyme with the same subunit properties and c-subunit/holoenzyme stoichiometry.